Reaktualisasi Etika Pendidikan di Era Digital: Tantangan dan Strategi Pembentukan Karakter - Ahmad Maulana Ali Fikri; Ahmad Ma’ruf Mudzakir Akbar; Agil Assakina Zahra (CV Omah Kreator, 2025)
Teachers play a crucial role as educators and moral exemplars in shaping students’ character within the school environment. As figures of integrity, teachers are responsible not only for transferring knowledge but also for instilling ethical values and noble character through their behavior and attitudes. However, cases of ethical misconduct such as bullying among teachers and students indicate a moral crisis in education. This situation undermines teachers’ authority and negatively affects students’ moral development. Therefore, strengthening ethics in educational practice is essential to restore moral order in schools. Character education should be instilled from an early age, especially in elementary schools, as the foundation for moral and personal development. The implementation of teacher ethics aligns with UNESCO’s four pillars of education learning to know, learning to do, learning to be, and learning to live together which emphasize the balance between knowledge, skills, and humanity. In the context of Indonesian education, Ki Hadjar Dewantara’s philosophy remains relevant, positioning teachers as role models who integrate cognitive (cipta), affective (karsa), and psychomotor (karya) aspects to develop holistic human potential through ethical and character-based education.